2021
DOI: 10.1292/jvms.20-0596
|View full text |Cite
|
Sign up to set email alerts
|

DNA-based detection of <i>Leptospira wolffii</i>, <i>Giardia intestinalis</i> and <i>Toxoplasma gondii</i> in environmental feces of wild animals in Korea

Abstract: Leptospira , Giardia intestinalis and Toxoplasma gondii infections are reported in humans and animals worldwide, but molecular surveillance of these pathogens in Korean wildlife is still limited. Here, we examined the prevalence of these pathogens in environmental feces of Eurasian otters, leopard cats and raccoon dogs using nested PCR followed by DNA sequencing. G. intestinalis was detected in all of three animals, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
7
2
Order By: Relevance
“…This study showed that the prevalence of G. duodenalis was relatively low compared with the results of previous studies in the ROK [25,27,[30][31][32]. Moreover, the infection rate of G. duodenalis was considerably lower than that reported globally [3,13,33,34].…”
Section: Discussioncontrasting
confidence: 58%
“…This study showed that the prevalence of G. duodenalis was relatively low compared with the results of previous studies in the ROK [25,27,[30][31][32]. Moreover, the infection rate of G. duodenalis was considerably lower than that reported globally [3,13,33,34].…”
Section: Discussioncontrasting
confidence: 58%
“…Notably, the rates of Giardia infection in wild boars have been reported to be 40.7% in Poland, 22.5% in southern Spain, 3.1% in China, 1.7% in Croatia, and 1.3% in northwestern Spain (17, 23,24,36,37). However, no studies have been (27).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of Giardia infections in wild boars and domestic pigs have been conducted worldwide (17, [21][22][23][24]. However, research on Giardia in Korea has mainly focused on environmental samplesincluding drinking water, cattle-like livestock animals, and companion animals, such as dogs-and studies on wild animals are lacking (25)(26)(27)(28)(29). No studies have been conducted on Giardia infections in wild boars, and only one study is available on domestic pigs (30).…”
mentioning
confidence: 99%
“…We analyzed 18 fecal samples of Eurasian otters ( N = 7) and leopard cats ( N = 11). The samples in this study have been studied in our previous studies for analyses of diet [ 15 ] and zoonotic parasites [ 16 ]. The location of fecal sampling is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%